2020
DOI: 10.1080/23802359.2020.1789512
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitogenome of the Lepturacanthus savala (Perciformes: Trichiuridae) from the Yellow Sea

Abstract: Lepturacanthus savala is a commercially important marine fish belonging to the family Trichiuridae, with a wide distribution in the Indian-Western Pacific coastal waters. In this study, the complete mitochondrial genome of L. savala has been determined by primer walking methods. The mitogenome is 17,146 bp in length containing 13 protein-coding genes, 2 ribosomal RNA genes, 21 transfer RNA genes, a control region, and an origin of light-chain replication region. The base composition is 28.9% for A, 29.0% for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…MW694877, 15688), E. muticus (No. MN067886.1, 18251), and L. savala (MT269921, 17146) have been reported in the previous study (Liu and Cui, 2009;Fan et al, 2019;Cai et al, 2020). The genome length of four Trichiuridae species in this study was shorter than the reported sequences except for T. brevis.…”
Section: Figurementioning
confidence: 38%
“…MW694877, 15688), E. muticus (No. MN067886.1, 18251), and L. savala (MT269921, 17146) have been reported in the previous study (Liu and Cui, 2009;Fan et al, 2019;Cai et al, 2020). The genome length of four Trichiuridae species in this study was shorter than the reported sequences except for T. brevis.…”
Section: Figurementioning
confidence: 38%
“…L. savala is also clearly distinguished from other teleost fishes and can be considered a special case in the genetic evolution of teleosts. Previous studies of L. savala have mainly focused on fishery resources [ 28 , 36 ], biological characteristics [ 32 ], feeding habits [ 37 ], mitochondrial DNA [ 38 ], and population genetics [ 39 ]. However, the molecular mechanisms underlying the evolution of its unique traits have not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%